The Strategy to Increase Added Value of Bamboo Shoots Through Diversification of Processed Bamboo Stick Products (Bamboo Stick Toothpicks) and Bamboo Shoot Crackers - Hernisawati; Febriliana Rika Anjani; Firman; Layla Nur Zakia; Fahrul Husaini; Agung Saputra (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2025)
Bamboo shoots are one of the non-timber forest products that have very high economic potential. However, the use of bamboo shoots is currently still limited to direct consumption as vegetables. This study aims to explore strategies to increase the added value of bamboo shoots through diversification of processed products, especially in the form of cucuk gigi and bamboo crackers. The methods used in this study include descriptive-qualitative and quantitative approaches, with several stages such as literature studies, interviews, product analysis trials, SWOT, and organoleptic tests. The results of the study indicate that cucuk gigi made from bamboo shoots produces a strong, hygienic, and environmentally friendly product as an alternative to wood. On the other hand, bamboo shoot crackers offer a crunchy texture and distinctive taste that has the potential to be well received by the market. The SWOT analysis shows that product diversification can increase the competitiveness of bamboo shoots in the market, create new economic opportunities, and optimize the use of natural resources sustainably. Recommended strategies include improving production technology, digital promotion, and developing business partnerships to support industries based on natural resources.